Why Must We Conserve Wildlife? - Ulloa G., José A. (Spei Domus, 2012)
The current crisis of biodiversity loss, observed in the loss of wild flora and fauna, among other things, represents a threat to the future health and prosperity of humanity. Wildlife, as a fundamental component of biodiversity and ecosystems, is an important factor to consider as part of the process of reflection that is the aim of this article. Despite current interest in this topic, there is a lack of clarity about what wildlife signifies, whether it benefits or is detrimental to humans and whether it should be conserved, and why. There is therefore a need to begin to rethink our approach to valuing biodiversity and to seek common ground regarding the priorities that must be established for the use of available human and financial resources in search of present and future health and prosperity. This opinion paper aims to provide information as a starting point for reflection, describing some of the views (mainly utilitarian) on wildlife and its value as seen in diverse social sectors, and to present the author’s opinion about the degree of relevance that should be placed on wildlife conservation, in a context that mainly takes human objectives into account.
Keywords: barrier; conservation; disease; existence; value